United States : Financial Sector Assessment Program-Stress Testing-Technical Notes. (IMF Staff Country Reports; Country Report ;, 2015)
This Technical Note discusses key findings of stress testing on the United States under the Financial Sector Assessment Program. Several stress tests were used to quantify the potential impacts of risks and vulnerabilities in banking and non-banking sectors. The stress tests run by the authorities and by companies under the Dodd-Frank Act (DFA) suggest that most large bank holding companies (BHCs) are resilient to shocks similar to the last crisis. For BHCs, the IMF staff's solvency stress tests over the initial stressed period are largely in line with the DFA stress testing results, and suggest that the system is generally robust, although some BHCs would fall below the hurdle rate in the stressed environment.